Underground explosions: estimating the safe distance. Issue 3 (7th September 2016) - Zimbelmann, Jörg; Boley, Conrad
Abstract : Underground explosions may contain an even more devastating potential than comparable free explosions in air, because they can produce significantly greater pressures and stronger momenta and the explosive waves may decay more slowly with increasing distance. For civil applications such as clearance of explosive ordnance, explosive tunnelling and surface mining in the vicinity of buildings, a tool is desirable, with which the safe distance r hor, safe, beyond which a building remains undamaged, may be evaluated in a fast and simple manner. The procedure to derive such a tool is exemplarily demonstrated for near-surface, underground explosions with a charge mass of 125 kg of trinitrotoluene, dry sand as foundation soil and a building with shallow foundation and no basement. Numerical simulations were carried out with the commercial hydrocode Autodyn. To track the explosion-induced wave up to sufficiently large distances, the modelling strategy called the 'moving window' was developed. With respect to the damage patterns, 'air blast', 'foundation-induced excitation of the structure to vibrations' and 'inadmissible inclination of foundations due to subsidence', the numerical time courses of the relevant wave parameters were evaluated. The result is one chart for the safe distance as a function of the explosive's charge depth.